E-BUSINESS DAN E-COMMERCE SEBAGAI TREND TAKTIK BARU PERUSAHAAN - Harisno, Harisno; Pujadi, Tri (CommIT (Communication and Information Technology) Journal, 2009)
Nowadays, the technology rapidly develops. Renewable trend, some companies use Internet-based applications to support product marketing. Not only on promotion activities in order to display the products known by their customers, even some companies use this technology to support transactions, such as selling products to consumers. At present various ways of Internet-based transactions are often found as E-Payment, E-Transaction, E-Money and others, which aims to serve the entire world. E-Commerce is part of the E-Business is used by many corporations and individuals. This research introduced a method of marketing and Internet-based transactions. Examples include using a web blog. It also will discuss the differences between the E-Business with E-Commerce.Keywords: E-Business, E-Commerce, technology